Fecal Microbiota Transplantation and Health Outcomes: An Umbrella Review of Meta-Analyses of Randomized Controlled Trials - Li, Yapeng; Zhang, Tingting; Sun, Jiahui; Liu, Nanyang (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Meta-analysis of randomized clinical trials (RCT) demonstrated several health benefits of fecal microbiota transplantation (FMT). However, there has been little comprehensive assessment of the strength and quality of evidence. We conducted an umbrella review to summarize the evidence of the association between FMT and health outcomes. Methods: PubMed, Embase, and Cochrane library databases were searched from inception to August 6, 2021. The random-effects model was applied to recalculate the effect estimates. We used AMSTAR 2 and GRADE to assess the methodological quality and to grade the evidence. Results: A total of 7 meta-analyses comprising 26 RCTs (median [IQR] primary study, 6 [2-7]; median [IQR] sample size, 267 [147-431] participants) were included in the current umbrella review describing 45 unique associations. There were 22 statistically significant associations (49%) demonstrating beneficial outcomes of FMT for antibiotic resistance burden, functional constipation, inflammatory bowel disease, and C. difficile infection. FMT does not appear to be associated with positive outcomes in irritable bowel syndrome and metabolic syndrome. Eight significant associations (36%) were supported by moderate-quality evidence, nine associations (41%) were supported by low-quality evidence, and the remaining associations found to be significant were supported by very low-quality evidence. Conclusion: Although we found that FMT was positively associated with several outcomes, caution should be exercised in choosing this approach, given the insufficient number of primary studies, low methodological quality, and low quality of evidence. Further high-quality randomized controlled trials with long-term follow-up are needed to improve the strength and credibility of the evidence base.